The best yes [compact disc, unabridged] : making wise decisions in the midst of endless demands - TerKeurst, Lysa (Thomas Nelson, Inc., 2014)
The best yes is the choice that shapes all other choices. (And those choices determine the direction of lives.) It's what allows listeners to play their necessary parts in God's plan, to spend their energy and focus their passion on the assignments that really are theirs. How do listeners learn to say that best yes? It requires honesty. Imagination. Attention. Trust. Humility. Practice-lots of practice. And wisdom. The best yes is really all about wisdom-learning to make truly wise decisions.